1990
DOI: 10.1007/bf01407512
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged adenomectomy for enclosed prolactinomas: A preliminary study of 26 cases

Abstract: Preliminary results obtained from 26 cases of prolactinomas less than 20 mm in diameter after treatment by enlarged adenomectomy are described. The operation consisted in removal of the adenoma, a layer of normal pituitary at the outer edge of the tumour and the pituitary capsule in contact with the sellar meninges. 24 women and 2 men were involved whose prolactin levels (PRL) were less than 200 ng/ml. All presented abnormal PRL responses to Thyrotropin releasing hormone (TRH) and Metoclopramide (MCP) tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…Moreover, extension of tumoral tissue into the peritumoral rim in patients in remission suggests that removal of macroscopically normal pituitary tissue around the visible lesion might have been beneficial in these patients. Similar observations have been made in other types of pituitary adenomas (21). Unlike other authors (7), we found no evidence of corticotroph hyperplasia in the specimens analyzed.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Moreover, extension of tumoral tissue into the peritumoral rim in patients in remission suggests that removal of macroscopically normal pituitary tissue around the visible lesion might have been beneficial in these patients. Similar observations have been made in other types of pituitary adenomas (21). Unlike other authors (7), we found no evidence of corticotroph hyperplasia in the specimens analyzed.…”
Section: Discussioncontrasting
confidence: 49%
“…An enlarged adenomectomy, removing the adenoma and the surrounding parenchyma, was performed as described previously (21). Before the adenoma was sought or penetrated, the two lateral wings were dissected, the surgeon keeping the approach outside the capsule.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation